(untitled) (Journal of Engineering, 2006)
A numerical study of mixed convtion cooling of heat dissipating electronic component, located in a rectangular enclosure, and cooled by an external through flow of air is carried out.A conjugate problem is solved by primitive variables method, describing the flow and thermal fields in air .The interaction between the components is of interest here, depending on their relative placement in the enclosure, and different configuration are considered. for Re=100 laminar, steady flow is predicted for up to Gr/Re2 =25 according to heat source location in the enclosure. The mixed convection regime, where the buoyancy effects are comparable to the forced flow, occurs at values of Gr/Re2 between 0.01 and 25 .The results are of values in search for suitable placement of electronic components in an enclosed region for an effective heat removal. In general, it appears that the location of the source on the left vertical wall is the most favorable in terms of cooling. Laminar results are predicted up for up to Gr = 2.5*105 for all configurations studied